Specialist service for the provision of opthalmic benefit (letter) - Harwood, E. G.
1929-11-26 1929 1920s 3 pages -3- as soon as practicable, and the Board also proposes to secure the representation of the non-insured element of the population coming within the scope of the scheme. The Service may be utilised by those Approved Societies which include ophthalmic benefit among their additional benefits, and a number of societies have already adopted the scheme - the Board is given to understand that other societies will adopt the Scheme after the present valuation period. The Board is anxious however that all members of the public who come within the scope of the scheme should be made aware of the facilities offered, and it is with this object in view that I have been instructed to write to you. Owing to financial and other considerations the Board is precluded from any general advertising, and many are deprived through ignorance of the ophthalmic treatment now provided for them. The Board therefore would welcome the assistance of the Trades Union Congress in making known to their members the existence of this national scheme. I should be very pleased to go into the matter more fully by correspondence or to discuss the scheme personally by appointment if desired. Yours faithfully, E.G. Harwood General Secretary 292/841.4/1/57